Strategi Dan Tantangan Pendidikan Dalam Membangun Integritas Anti Korupsi Dan Pembentukan Karakter Generasi Penerus Bangsa - Zainudin Hasan; Bagas Satria Wijaya; Aldi Yansah; Rian Setiawan; Arya Dwi Yuda (Universitas Sains dan Teknologi Komputer, 2024)
This research explores strategies and challenges in education to build integrity, anti-corruption, and shape the character of the nation's next generation. A literature study approach is used to collect and analyze information from various sources such as books, research journals, and related articles. The research results show that humanistic education and anti-corruption education play an important role in shaping the character and positive attitudes of the younger generation. However, in the digital era, new challenges arise with the influence of information technology on character formation. An active role from educators, parents and society is needed to overcome this challenge and create an environment that supports the formation of strong character. Apart from that, anti-corruption education is also faced with challenges in integrating an understanding of corrupt practices in the educational environment itself. In conclusion, education has a very important role in forming the next generation with integrity and ethics, but a holistic and collaborative approach is needed to face the challenges of the times.